Study of SUMO-2-interacting motifs in Kaposi's sarcoma-associated herpesvirus - Costa, Catarina Neves (2021)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is one of the seven viruses able to cause cancer in humans. It displays a biphasic life cycle, in which the latent phase is regulated by the latency-associated nuclear antigen (LANA or kLANA), where the viral episome is maintained with limited gene expression inside the nucleus of the host B cell. During the lytic phase, viral gene products are systematically synthetized due to a time-controlled mechanism, which is activated by RTA (replication and transcription activator). SUMOylation is a reversible post-transcriptional modification involving SUMO (small ubiquitin-like modifier) proteins. A previous study in B lymphoma cells showed that kLANA contains a SUMO-interacting motif (LANASIM) that facilitates its own SUMOylation at lysine 1140. This motif also interacts with SUMO-2 modified transcription repressor KAP1, forming a transcriptional inhibitory complex along with Sin3A at the Rta gene promoter. LANASIM mutants led to loss of viral episome maintenance and lytic gene silencing. In this study, the aim was to assess the importance of LANASIM using an in vivo animal infection model. Considering the functional homology between murine herpesvirus-68 (MHV-68) mLANA and KSHV kLANA, LANASIM loss of function mutations were introduced into two MHV-68 chimeras. One where the mLANA coding sequence was replaced with the one from kLANA (v-kLANA SIM) and another where additionally the kLANA DNA binding domain was replaced with the one from mLANA (v-KM SIM).